The program of psychological rehabilitation of persons with acquired disorders of the musculoskeletal system - Tatyana N. Razuvaeva; Anna V. Lokteva; Julia N. Gut; Eugenia P. Pchelkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The study of factors influencing the success of rehabilitation of persons with acquired musculoskeletal disorders acquired in adulthood is determined by the increasing role in the psychological support and integration of such individuals into society, as well as the lack of methodological approaches and proven recommendations aimed at improving the rehabilitation process. The paper presents the psychological characteristics of people with musculoskeletal disorders acquired in adulthood. According to the results of psychodiagnostic examination, the program of psychological support for persons with musculoskeletal disorders has been developed. The aim of the study was to study the psychological characteristics of persons with acquired disorders of musculoskeletal disorders, to develop and evaluate the effectiveness of the program of psychological rehabilitation. We used the following research methods: clinical and psychological, psychodiagnostic, statistical, methods of analysis of empirical data. The ascertaining study was carried out with two groups: with disorders of the musculoskeletal disorders and without violations of the musculoskeletal disorders (the total number of participants was 60 people). Diagnostic tools: questionnaire Adaptability (A.G. Maklakov, S.V. Chermyanin), Freiburg personality questionnaire (modified by A.A. Krylov, T.I. Ronginskaya), Style of self-regulation of behavior (V.I. Morosanov), Test of resilience (S. Maddy, adaptation by DA Leontiev). Statistical data processing was carried out using the following criteria: Mann-Whitney U-test, Wilcoxon T-test using SPSS Statistics 19. It was revealed that persons with acquired disorders of musculoskeletal disorders are characterized by low adaptive abilities, an increased level of neuropsychic stress. Characterized by an insufficient level of self-regulation, the ability to consciously plan activities. It is determined that resilience is characterized by low involvement, insufficient ability to overcome life difficulties. It is shown that a personal factor that enhances maladjustment is low contact, emotional tension when interacting with others. The proposed program of psychological assistance to persons with disorders of the musculoskeletal system helps to overcome passivity, alienation; the formation of independence, responsibility, an active life position, a system of value orientations, strengthening of social position, and, ultimately, successful social adaptation.